Public Service Innovation PT. POS Indonesia in the Existence of Delivery Service Competition - Andi Molang Chaerul Kambau; Harsya Harun; Andi Meriam; Dewi Astika (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2023)
PT. POS Indonesia’s public service innovation in delivery service competition (Study at PT. POS Indonesia Palopo City branch). In competitive business world, particularly those focus on goods delivery services, the innovation demand was a central aspect needs concern, in particular of technological advances. This paper aims to discover why public of Palopo City tend to apply private shipping services instead of PT. POS and how it’s business innovation to face competition. The research was conducted on qualitative with descriptive approach. The results of the study was indicate that there was an interconnection relationship and influence on the delivery preference of goods based on information technology which has mostly been used by PT POS Indonesia's competitors. On the other hand PT. POS Indonesia was trying to maintain it’s existence by strengthening innovation in both products and processes, and the business aimed to upgrade competitiveness with other delivery service providers